Dimensions of Pay Satisfaction as Predictors of Work Engagement among Military and Civilian Personnel - Olusola, Akinbobola I.; Nathaniel, Nze D. (Journal of Reviews on Global Economics, 2019)
At the turn of the 21st Century, the world of work is experiencing phenomenal changes both at the workplace and in its work force. The reward output provided by organization may not commensurate with the input of personnel. This study therefore examined the predictability of dimensions of pay satisfaction on work engagement among military and civilian personnel in a Military Hospital in Nigeria. This study adopted cross-sectional survey utilizing an ex-post facto research design. A purposive sampling method was used to draw 256 participants comprising of 101 (39.5%) military and 155 (60.5) civilian personnel who completed structured psychological tests. Multiple regression and independent t test were used to analyse the data collected. The result showed that all the four dimensions of pay satisfaction which are (pay level, benefit, raise, and pay structure) jointly accounted for 16.7% of the total variation in work engagement. It is only one of the four dimensions of pay satisfaction (pay structure) that showed independent significant prediction of work engagement. Military personnel did not significantly manifest higher level of work engagement than civilian personnel. The implications of the result were discussed in line with management and sustainability of employment relationships in the world of work.